Respiratory impact of a grand tour: insight from professional cycling - Allen, H.; Price, O. J.; Greenwell, J.; Hull, J. H. (European Journal of Applied Physiology, 2021)
Purpose: The aim of this study was to evaluate the respiratory function and symptom perception in professional cyclists completing a Grand Tour (GT). Methods: Nine male cyclists completed La Vuelta or Tour de France (2018/19). At study entry, airway inflammation was measured via fractional exhaled nitric oxide (FeNO). Respiratory symptoms and pulmonary function were assessed prior to the first stage (Pre-GT), at the second rest day (Mid-GT) and prior to the final stage of the GT (Late-GT). Sniff nasal inspiratory pressure (SNIP) was assessed at pre and late-GT timepoints. Results: Seven cyclists reported respiratory symptoms during the race (with a prominence of upper airway issues). Symptom severity increased either mid or late-GT for most cyclists. A decline in FEV1 from pre-to-mid GT (- 0.27 ± 0.24 l, - 5.7%) (P = 0.02) and pre-to-late GT (- 0.27 ± 0.13 l, - 5.7%) (P < 0.001) was observed. Similarly, a decline in FVC (- 0.22 ± 0.17 l, - 3.7%) (P = 0.01) and FEF25-75 (- 0.49 ± 0.34 l/s, - 11%) (P = 0.02) was observed pre-to-late GT. Overall, eight (89%) and six (67%) demonstrated a clinically meaningful decline (> 200 ml) in FEV1 and FVC during the GT follow-up, respectively. SNIP remained unchanged pre-to-late GT (n = 5), however, a positive correlation was observed between DeltaSNIP and DeltaFVC (r = 0.99, P = 0.002). Conclusion: GT competition is associated with a high prevalence of upper respiratory symptoms and a meaningful decline in lung function in professional cyclists. Further research is now required to understand the underpinning physiological mechanisms and determine the impact on overall respiratory health and elite cycling performance and recovery.